Comparative Analysis of The Implementation Of Conventional And Modular Methods On Walls And Floor Plates In Terms Of Cost And Time (Case Study: Construction Of Satpol PP Building) - Firdaus Nurfuadi (Indonesian Journal Publisher, 2024)
Building construction requires selecting efficient construction methods to achieve the desired project objectives. This research aims to compare conventional and modular construction methods in the implementation of walls and floor plates, with a focus on cost and time analysis. The case study taken is the construction of the Satpol PP Building. This research method uses a quantitative approach by collecting primary and secondary data. Primary data was obtained through field observations and interviews with parties involved in the project, while secondary data was obtained from project documents, literature and other related references. Data analysis was carried out with comparing the total costs and time required for each construction method.